Evaluation of Bioactive Compounds in Bean Oils (Phaseolus vulgaris L.), Pérola and BRS Valente Varieties - Umeda, Wellington M.; Moreno Luzia, Debora Maria; Jorge, Neuza (Current Nutrition & Food Science, 2018)
Background: Bean is a leguminous widely consumed in the world by most of its population and different nutritional, antioxidant and functional properties are associated in it. Besides being one of the most traditional foods in the Brazilian diet. Objective: Thus, this study aims to evaluate the bioactive constituents (phytosterols, tocopherols, essencial fatty acids) in oils extracted from two bean varieties when submitted to different treatments (Raw, macerated and macerated/cooked). Methods: The oils extracted from two bean varieties, Pérola (carioca) and BRS Valente (black) with the three treatments were evaluated and analyzed for the composition of phytosterols, tocopherols and fatty acids to investigate the losses during domestic processing. Results: The phytosterols that were found in greater quantities were: campesterol, stigmasterol and β-sitosterol. It was highlighted the macerated/cooked black beans with the highest concentration of total phytosterols. It is possible to emphasize high amount of total tocopherols in the two varieties of beans for the macerated / cooked treatment. It is also worth noting the predominance of γ-tocopherol on the other isomers. In relation to fatty acids, the predominance of unsaturated and polyunsaturated fatty acids was observed, with emphasis on the presence of α-linolenic acid (ω3), important from a nutritional point of view, since it is an essential fatty acid. Conclusion: Based on the results obtained, it is possible to show the nutritional importance of the beans consumption studied in the Brazilian diet, by the bioactive constituents, still present after the heat treatment used.
Keywords: leguminous